Biochar-mediated reductions in greenhouse gas emissions from soil amended with anaerobic digestates - Martin, Sarah L.; Clarke, Michèle L.; Othman, Mukhrizah; Ramsden, Stephen J.; West, Helen M. (Elsevier, 2015)
This investigation examines nitrous oxide (N2O) fluxes from soil with simultaneous amendments of anaerobic digestates and biochar. The main source of anthropogenic emissions of N2O is agriculture and in particular, manure and slurry application to fields. Anaerobic digestates are increasingly used as a fertiliser and interest is growing in their potential as sources of N2O via nitrification and denitrification. Biochar is a stable product of pyrolysis and may affect soil properties such as cation exchange capacity and water holding capacity. Whilst work has been conducted on the effects of biochar amendment on N2O emissions in soils fertilised with mineral fertilisers and raw animal manures, little work to date has focused on the effects of biochar on nitrogen transformations within soil amended with anaerobic digestates. The aim of the current investigation was to quantify the effects of biochar application on ammonification, nitrification and N2O fluxes within soil amended with three anaerobic digestates derived from different feedstocks. A factorial experiment was undertaken in which a sandy loam soil (Dunnington Heath series) was either left untreated, or amended with three different anaerobic digestates and one of three biochar treatments; 0%, 1% or 3%. Nitrous oxide emissions were greatest from soil amended with anaerobic digestate originating from a maize feedstock. Biochar amendment reduced N2O emissions from all treatments, with the greatest effect observed in treatments with maximum emissions. The degree of N2O production and efficacy of biochar amelioration of gas emissions is discussed in context of soil microbial biomass and soil available carbon.